Tips in Making Documentary - Shu Voon, Ding; Chong Lee, Yow (Mini Film Festival, 2022)
Infographics on "tips in making documentary". The content is extracted from MFF Doc Workshop (3) presented by Mr. Yosep Anggi Noen, designed by Shu Voon, advised and edited by Yow.